Nature of radio-wave radiation from particle cascades - James, Clancy (AMER PHYSICAL SOC, 2022)
The nature of the radio-wave radiation generated by particle cascades in both the Earth's atmosphere and dense media such as ice has, historically, been much debated. This situation changed in 2010, with the community converging on the common terminology of "geomagnetic"and "Askaryan"radiation to describe the two emission mechanisms. However, this convergence arose from discussions at various conferences and workshops, and was ultimately reached through agreement between simulation codes and experimental measurements. In this article therefore, I use relatively simple geometrical arguments, and a minimum of calculations based on single particle tracks, to explain the nature of radiation from extensive air showers (EAS) and cascades in dense media such as ice. I identify well-determined frequency regimes where the radiation from the Askaryan effect will be bremsstrahlung-like and Cherenkov-like, being respectively below/above 1 GHz in EAS and 100 MHz in dense media; and where geomagnetic emission will be transverse-currentlike and where it will resemble synchrotron radiation, respectively below/above a few GHz in EAS, depending on the height of cascade development. I suggest how these transitions in the nature of the emission may be experimentally observed.